Forecasting Unemployment Rates in the Ilocos Region, Philippines, Using Time Series Analysis - Denver Q Narvasa (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Unemployment rates in the Ilocos Region are continuously progressing alongside the data-driven policymaking and strategies for the economy. This study presents a forecasting model that aims to forecast unemployment trends and propose measures to create more job opportunities, enhance workforce skills, and recommend strategies to reduce unemployment in the Ilocos Region. Utilizing time series analysis across the five different models, the ARIMA (1,1,1) model was identified as the most suitable in forecasting unemployment rates over time. Results also indicate that this approach can informed can be made effectively on the unemployment issues. This research helps Filipino economists, encouraging them to come up with new implementing strategies and interventions to enhance economic well-being in the Ilocos Region and the Philippines.